Traditional knowledge of biodiversity in the community surrounding Giam Siak Kecil-Bukit Batu Biosphere Reserve, Riau, Indonesia - Herman Suparman Simanjuntak; Endang Sukara; Dolly Priatna (Indonesian Journal of Applied Environmental Studies, 2021)
The Objective of this study is to analyze the potential for biodiversity and traditional knowledge in the buffer zone of the Giam Siak Kecil-Bukit Batu Biosphere Reserve (GSK-BB). The research was conducted descriptively-quantitatively by analyzing two variables, i.e. biodiversity and community traditional knowledge. Biodiversity monitoring report documents from PT Sakato Pratama (PT SPM) and PT Bukit Batu Hutan Alam (PT BBHA), profiles of Temiang and Sepahat villages, questionnaire data taken from village community representatives, as well as the results of in-depth interviews were used in the analysis. The results show that in the PT SPM area, there are 177 species of plants and 55 species of animals. Meanwhile in the PT BBHA area there are 146 species of plants and 46 species of animals. Based on information from the community of Temiang Village, there are 51 species of plants and 18 species of animals, while according to the people of Sepahat Village, there are 73 species of plants and 83 species of animals. The biodiversity utilized by the community in the two villages consists of 36 species of plants and 15 species of animals, but only three species are wild animals, i.e. sun bear (Helarctos malayanus), horseshoecrab (Limulus sp.), and seahorse (Hippocampus sp.) .), and one species of plant (rattan, Calamus sp.). The rest are cultivated plants and livestock. From the analysis, it can be concluded that the relationship between biodiversity and traditional knowledge in both Temiang and Sepahat Villages is very limited. Awareness of the strategic value of wild plants and wildlife in the buffer zone of the biosphere reserve needs to be increased.Penelitian ini bertujuan untuk menganalisis potensi keanekaragaman hayati dan pengetahuan tradisional di zona penyangga Cagar Biosfer Giam Siak Kecil-Bukit Batu (GSK-BB). Penelitian dilakukan secara deskriptif-kuantitatif dengan menganalisis dua variable, yaitu keanekaragaman hayati dan pengetahuan tradisional masyarakat. Dokumen laporan monitoring keanekaragaman hayati dari PT Sakato Pratama (PT SPM) dan PT Bukit Batu Hutan Alam (PT BBHA), profil Desa Temiang dan Sepahat, data kuisioner yang diambil dari perwakilan masyarakat desa, serta hasil wawancara mendalam digunakan dalam analisis. Hasil menunjukan bahwa di kawasan PT SPM tercatat terdapat 177 jenis tumbuhan  dan 55 jenis satwa. Sementara itu di kawasan PT BBHA terdapat 146 jenis tumbuhan dan 46 jenis satwa. Berdasarkan informasi dari masyarakat Desa Temiang terdapat 51 jenis tumbuhan dan 18 jenis satwa, sedangkan menurut masyarakat Desa Sepahat terdapat 73 jenis tumbuhan dan 83 jenis satwa. Keanekaragaman hayati yang dimanfaatkan oleh masyarakat di kedua desa tersebut terdiri atas 36 jenis tumbuhan dan 15 jenis satwa, namun hanya tiga jenis yang merupakan hewan liar, yaitu beruang madu (Helarctos malayanus), belangkas (Limulus sp.), dan kuda laut (Hippocampus sp.), serta satu jenis tumbuhan (rotan, Calamus sp.). Selebihnya merupakan tanaman budidaya dan hewan ternak. Dari hasil analisis,  dapat ditarik  kesimpulan sementara bahwa hubungan keanekaragaman hayati dengan pengetahuan tradisional di kedua desa Temiang dan Sepahat sangat terbatas. Kesadaran tentang nilai strategis tumbuhan dan satwa liar yang ada di kawasan penyangga cagar biosfer perlu ditingkatkan.